Peningkatan Kemampuan Kreativitas Menggambar Melalui Metode Bercerita Pada Anak Kelompok B Semester I TK Kemala Bhayangkari 53 Ngawen Kecamatan Ngawen Kabupaten Blora Tahun 2015/2016 - SULISTYOWATI, SULISTYOWATI, Drs. M. Yahya, M.Si (2015)
This study aims to improve the ability to draw children's creativity through storytelling. This research is a classroom action research conducted in two cycles and each cycle outsmart conducted two meetings. The subjects of this study are Group B kindergarten children Kemala Bhayangkari 53 Ngawen District of Ngawen Blora totaling 13 children as recipients of actions, researcher and teacher colleagues as giving action. The data collected in this study is data about the ability of children's creative drawing and data on teacher learning through storytelling. Both of these data were collected through observation. Data's ability to draw a child's creativity analyzed by comparative analysis and data on teacher learning through storytelling method were analyzed by interactive analysis. The results of the analysis showed that the average prasiklus creative ability to draw the child reaches 47% means that the ability to draw new children's creativity began to flourish. After the first cycle measures the average ability of creativity to draw the child reaches 67%, which means that the child's ability to creatively draw already increased to evolve as expected. After the second cycle measures the average child's ability to creatively draw increased 82% means the ability of developing children's creativity draw very good. Main of this study is that through storytelling methods can enhance children's ability to creatively draw in Group B TK Kemala Bhayangkari 53 Ngawen District of Ngawen District Blora.